High-energy resummation in semi-hard processes at the LHC - Celiberto, Francesco Giovanni; Carbone, Vincenzo; Papa, Alessandro (My University, 2017)
Semi-hard processes in the large center-of-mass energy limit offer us an exclusive chance to test the dynamics behind strong interactions in kinematical sectors so far unexplored, the high luminosity and the record energies of the LHC providing us with a richness of useful data. In the Regge limit, s jtj, fixed-order calculations in perturbative QCD based on collinear factorisation miss the effect of large energy logarithms, which are so large to compensate the small QCD coupling s and must therefore be accounted for to all perturbative orders. The BFKL approach represents the most powerful tool to perform the resummation to all orders of these large logarithms both in the LLA, which means inclusion of all terms proportional to ( s ln(s))n, and NLA, which means inclusion of all terms proportional to s( s ln(s))n. The inclusive hadroproduction of forward jets with high transverse momenta separated by a large rapidity gap at the LHC, the so-called Mueller–Navelet jets, has been one of the most studied reactions so far. Interesting observables associated to this process are the azimuthal correlation momenta, showing a very good agreement with experimental data at the LHC. However, new BFKL-sensitive observables should be considered in the context of the LHC physics program. With the aim the to further and deeply probe the dynamics of QCD in the Regge limit, we give phenomenological predictions for four distinct semi-hard process. On one hand, we continue the analysis of reactions with two objects identified in the final state (i) by addressing open problems in the Mueller– Navelet sector and (ii) by studying the inclusive dihadron production in the full NLA BKFL accuracy. Hadrons can be detected at the LHC at much smaller values of the transverse momentum than jets, allowing us to explore an additional kinematical range, complementary to the one studied typical of Mueller– Navelet jets. Furthermore, this process permits to constrain not only the parton distribution functions for the initial proton, but also the parton fragmentation functions describing the detected hadron in the final state. On the other hand, we show how inclusive multi-jet production processes allow us to define new, generalised and suitable BFKL observables, where transverse momenta and rapidities of the tagged jets, well separated in rapidity from each other, appear in new combinations. We give the first phenomenological predictions for the inclusive three-jet production, encoding the effects of higher-order BFKL corrections. Then, making use of the same formalism, we present the first complete BFKL analysis for the four-jet production.
Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXIX
Keywords: Large Hadron Collider; Particles (Nuclear physics)